Pengaruh Shopping Lifestyle, Discount Dan Fashion Involvement Terhadap Impulse Buying Pada Online Shop Lazada.Co.Id ( Studi Kasus Pada Mahasiswa Feb Unisma ) - Andik Dewantoro; N. Rachma; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted to determine the effect of Shopping Lifestyle, Discounts, Fashion Involvement on Impulse Buying at Lazada.co.id Online Shop at the Faculty of Business Economics, Islamic University of Malang. This research uses explanatory research and quantitative approaches. Malhotra's theory is used to take samples, that is the number of items x 5 so that a total sample of 110 people is found.To solve the problem in this study, using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. research using multiple linear regression analysis with the help of SPSS 16 The results of this study are the Shopping Lifestyle, Discount, Fashion Involvement variables affect Impulse Buying simultaneously, partially the Shopping Lifestyle, Discount, Fashion Involvement variables affect the Impulse Buying at Lazada.co online shop. en at the Faculty of Business Economics, Islamic University of Malang. Keywords : Shopping Lifestyle, Discount, Fashion Involvement, Impulse Buying